High-Temperature Creep Behavior of a Nickel-Based Single-Crystal Superalloy with Small-Angle Deviation from [111] Orientation - Guangyan Wang; Song Zhang; Guoqi Zhao; Ning Tian; Huajin Yan; Sugui Tian; Fangwei Jin (Advances in Materials Science and Engineering)
By means of tensile creep tests and microstructure analysis, the creep behavior and deformation mechanism of a nickel-based single-crystal alloy with small-angle deviations from the [111] orientation at 1040°C/137 MPa were investigated. The results suggested that in the early stage of creep, proliferating dislocations generated by different slip systems get accumulated in the γ phase. Dislocations mainly slipped in the γ phase and climbed over the γ′ phase, and they began to form a dislocation network at the interface. γ′ phases were connected to each other, and the coherence relationship was destroyed. In the steady-state stage of creep, the solid interfacial dislocation network was formed, and the γ′ phase transformed into a lamellar raft structure, which hinders the slip and climb of dislocations in the matrix channel. In the accelerated creep stage, the dislocation network was destroyed, and dislocations sheared into the γ′ phase in the way of dislocation pairs, which could react to form a superdislocation node and decompose to form APBs on the <111> plane or cross slip from the <111> plane to the <100> plane to form K-W locks.